Evaluation of guanidine antifungal solutions for denture base resin: an in vitro study - Maria Eduarda Rodrigues Gama; Vicente Castelo Branco Leitune; Isadora Martini Garcia; Stéfani Becker Rodrigues; Fabrício Mezzomo Collares (Revista da Faculdade de Odontologia de Porto Alegre, 2020)
Background: The purposes of this study were: (1) to formulate polyhexamethylene guanidine hydrochloride (PHMGH) solutions at different concentrations; (2) to evaluate their antifungal activity against a mature biofilm of Candida albicans on acrylic resins; (3) to evaluate possible effects on acrylic resins flexural strength and surface roughness. Methods: PHMGH solutions were formulated with distilled water and 0.125, 0.250, or 0.5 wt.% of PHMGH. One group without PHMGH was used as control. For antifungal activity analysis, acrylic resin specimens were contaminated with C. albicans. Specimens were immersed in PHMGH solutions or distilled water for 5 or 10 min. Ultimate flexural strength and surface roughness of acrylic resins were evaluated. Results: All PHMGH solutions at 5 or 10 min showed antifungal activity compared to the control group (p